The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.2319/102715-722
|View full text |Cite
|
Sign up to set email alerts
|

Children's perceptions of smile esthetics and their influence on social judgment

Abstract: Smile esthetics influence social perception during childhood and adolescence. However, thresholds of smile esthetic acceptance in children and adolescents are still not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Tooth loss was the consequence that most negatively influenced the perception of the participants. This result is in agreement with other studies and can be justified because physical appearance is critical to teenagers and is valued more than any other lifestyle factor . Besides that, missing teeth have previously been identified as an important factor that influences adolescent's satisfaction with dental appearance and self‐esteem, as also seen in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Tooth loss was the consequence that most negatively influenced the perception of the participants. This result is in agreement with other studies and can be justified because physical appearance is critical to teenagers and is valued more than any other lifestyle factor . Besides that, missing teeth have previously been identified as an important factor that influences adolescent's satisfaction with dental appearance and self‐esteem, as also seen in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that the presence of gingivitis, characterized by clinical signs such as enlargement and gingival bleeding, affects the overall OHRQoL and the emotional and social well‐being domains 19,21 . In this sense, individuals who are ashamed of the aesthetic appearance of the smile tend to be less confident, withdrawn and have a low self‐esteem, 32 which may be related to a higher occurrence of bullying among classmates at school, and consequently reflecting in a worse OHRQoL 33 …”
Section: Discussionmentioning
confidence: 99%
“…Over the years, aesthetic demands have increased mainly in relation to aspects of the smile, 1 and especially to the presence of developmental defects of enamel (DDE). 2,3 These have been defined as qualitative or quantitative defects that occur during the phases of amelogenesis.…”
Section: Introductionmentioning
confidence: 99%